2018
DOI: 10.1002/lipd.12017
|View full text |Cite
|
Sign up to set email alerts
|

CETP and LCAT Gene Polymorphisms Are Associated with High‐Density Lipoprotein Subclasses and Acute Coronary Syndrome

Abstract: We evaluated whether CETP and LCAT gene polymorphisms are statistically associated with the high-density lipoprotein (HDL) size distribution, the cholesterol level of HDL subclasses, and the acute coronary syndrome (ACS) susceptibility. Two CETP gene polymorphisms (rs4783961 and rs708272) and one LCAT polymorphism (rs2292318) were genotyped by 5' exonuclease TaqMan assays in 619 patients with ACS and 607 control individuals. For HDL analysis, a subgroup of 100 healthy individuals was recruited; the HDL subclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(92 reference statements)
3
8
0
1
Order By: Relevance
“…This finding underscores the importance of not only population-level studies but also research on subjects with specific phenotypes of the lipid profile in order to determine the contribution of genetic factors to the predisposition to common diseases. These observations are consistent with the results of several studies [6,8,9]. For instance, Gilberto Vargas-Alarcon and coworkers demonstrated an association of allele G with a lowered HDL-C concentration and a higher risk of acute coronary syndrome (odds ratio = 1.45, p = 0.036) [8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding underscores the importance of not only population-level studies but also research on subjects with specific phenotypes of the lipid profile in order to determine the contribution of genetic factors to the predisposition to common diseases. These observations are consistent with the results of several studies [6,8,9]. For instance, Gilberto Vargas-Alarcon and coworkers demonstrated an association of allele G with a lowered HDL-C concentration and a higher risk of acute coronary syndrome (odds ratio = 1.45, p = 0.036) [8].…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the presence of allele G in various populations has been linked with changes in the activity of the CETP protein, thus leading to lower HDL-C levels, which can raise the risk of CVDs [6,8,9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Vargas-Alarcon et al revealed that this variant was not only associated with the risk of acute coronary syndrome but also with HDL-C levels and HDL subclasses in Mexican mestizos. [27] However, a prospective population-based study conducted in Caucasians demonstrated that CETP rs708272 was associated with increased levels of HDL-C, but not a decreased risk for CAD. [28] To avoid the poorly statistic efficiency caused by small sample size, several meta-analysis studies were also performed to clarity the associations of CETP rs708272 polymorphism and CAD risk and lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LCAT on human atherogenesis is controversial [113,114]. Genetic deficiency of LCAT leads to the accumulation of nascent pre-β HDL in the circulation and development of atherosclerosis and acute coronary syndrome [114,115,116,117,118,119,120,121]. In golden Syrian hamsters, the loss of LCAT activity led to dyslipidemia and atherosclerosis [122].…”
Section: Mechanisms For Increased Circulating Lysophosphatidylcholmentioning
confidence: 99%